2012
DOI: 10.1186/1746-4269-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-botanical study of the African star apple (Chrysophyllum albidum G. Don) in the Southern Benin (West Africa)

Abstract: BackgroundIn addition to plant species biology and ecology, understanding the folk knowledge systems related to the use of plant species and how this knowledge system influences the conservation of plant species is an important issue in the implementation of sustainable strategies of biodiversity conservation programs. This study aimed at providing information on the use and local knowledge variation on Chrysophyllum albidum G. Don a multipurpose tree species widely used in southern Benin.MethodsData was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…Various studies have reported on the ethnobotanical uses of indigenous fruits such as ackee ( Blighia sapida K.D. Koenig) in the treatment of fever, burns, anemia, vomiting, malaria, eye problems and snakebite [15], Marula ( Sclerocarya birrea ) in treating malaria, stomach-ache, diarrheoa, haemorrhoids cough and diabetes [20] and African star apple ( Chrysophyllum albidum G. Don) in the treatment of malaria, anaemia, ulcer, haemorrhoids, smallpox, asthma, cough, dental decay, yellow fever and avitaminosis [16]. Many of the plants based prescriptions by traditional healers or knowledge holders can be considered as general health tonics which can be used to treat general weakness and unspecified ailments [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported on the ethnobotanical uses of indigenous fruits such as ackee ( Blighia sapida K.D. Koenig) in the treatment of fever, burns, anemia, vomiting, malaria, eye problems and snakebite [15], Marula ( Sclerocarya birrea ) in treating malaria, stomach-ache, diarrheoa, haemorrhoids cough and diabetes [20] and African star apple ( Chrysophyllum albidum G. Don) in the treatment of malaria, anaemia, ulcer, haemorrhoids, smallpox, asthma, cough, dental decay, yellow fever and avitaminosis [16]. Many of the plants based prescriptions by traditional healers or knowledge holders can be considered as general health tonics which can be used to treat general weakness and unspecified ailments [26].…”
Section: Resultsmentioning
confidence: 99%
“…Indigenous fruit trees have been given only limited attention, both in research and development, though they are important in the diet [10]. These indigenous fruit trees play important roles in the lives of rural peoples in Namibia [11], Botswana [12], Zimbabwe [13], Ghana [14], Benin [15,16], and Ethiopia [17,18]. The consumption of indigenous fruits in Ohangwena and Oshikoto forms a daily life practice and it is gaining an increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…La plus grande contrainte quand à la conservation reste les modes d'utilisation des terres. Comme l'a souligné Houessou et al (2012), la regression de Chrysophyllum albidum au Sud du Bénin est liée en grande partie à la destruction de l'habitat naturel de l'espèce qui se retrouve aujourd'hui confiné dans les systèmes agroforestiers suite à l'urbanisation de plus en plus accélérée de cette partie du Bénin qui est le corollaire d'une croissance démographique galapante. De plus, la dynamique actuelle d'occupation des terres dans le secteur d'étude laisse déjà présager une régression des milieux naturels (vestige de forêt par exemple) au détriment des habitats (Oloukoi, 2006).…”
Section: Chrysophyllum Albidumunclassified
“…Apart from the fruit being consumed widely among Nigerians especially in the South‐western region, other parts of the plant have been reported useful in traditional medicine. Houessou, Toussaint, François, Gbesso Lisette, and Anagonou () reported the multipurpose nature of C. albidum as follows; its fleshy fruits are widely consumed and the different plant parts are used in folk medicine to treat several diseases and disorders and the fruits contribute to improving health, nutrition, food security, and income of the local communities. Amusa, Ashaye, and Oladapo () pointed out that across Nigeria, it is known by several local names and is generally regarded as a plant with diverse ethno‐medicinal uses.…”
Section: Introductionmentioning
confidence: 99%